A Plant Extract Acts Both as a Resistance Inducer and an Oomycide Against Grapevine Downy Mildew - Krzyzaniak, Yuko; Trouvelot, Sophie; Negrel, Jonathan; Cluzet, Stéphanie; Valls, Josep; Richard, Tristan; Bougaud, Ambrine; Jacquens, Lucile; Klinguer, Agnès; Chiltz, Annick; Adrian, Marielle; Héloir, Marie-Claire (Frontiers in Plant Science, 2018)
Protecting vineyards from cryptogamic diseases such as downy mildew, caused by Plasmopara viticola, generally requires a massive use of phytochemicals. However, the issues on unintentional secondary effects on environment and human health, and the occurrence of P. viticola resistant strains, are leading to the development of alternative strategies, such as the use of biocontrol products. In this paper, we evidenced the ability of a plant extract to protect grapevine from P. viticola. Further experiments carried out both on cell suspensions and on plants revealed that plant extract activates typical defense-related responses such as the production of H2O2, the up-regulation of genes encoding pathogenesis-related proteins and stilbene synthase, as well as the accumulation of resveratrol or its derivative piceid. We also brought to light a strong direct effect of PE on the release and motility of P. viticola zoospores. Furthermore, we found out that PE application left dried residues on leaf surface, impairing zoospores to reach stomata. Altogether, our results highlight the different modes of action of a new biocontrol product able to protect grapevine against downy mildew.